2012 Proceedings IEEE INFOCOM 2012
DOI: 10.1109/infcom.2012.6195636
|View full text |Cite
|
Sign up to set email alerts
|

How good is bargained routing?

Abstract: Abstract-In the context of networking, research has focused on non-cooperative games, where the selfish agents cannot reach a binding agreement on the way they would share the infrastructure. Many approaches have been proposed for mitigating the typically inefficient operating points. However, in a growing number of networking scenarios selfish agents are able to communicate and reach an agreement. Hence, the degradation of performance should be considered at an operating point of a cooperative game. According… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…It is clear that V (S) satisfies the conditions of an NTU coalitional game. Closedness follows directly from Assumption S2 and following [15], [16], it can be shown that V (S) is convex. Having defined the worst-case coalitional game, we proceed to investigate it through the study of several (fair and stable) solution concepts of cooperative game theory.…”
Section: Worst-case Coalitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is clear that V (S) satisfies the conditions of an NTU coalitional game. Closedness follows directly from Assumption S2 and following [15], [16], it can be shown that V (S) is convex. Having defined the worst-case coalitional game, we proceed to investigate it through the study of several (fair and stable) solution concepts of cooperative game theory.…”
Section: Worst-case Coalitionsmentioning
confidence: 99%
“…Accordingly, the performance degradation of such systems should be considered at new operating points. In the realm of routing games, such an operating point has been proposed in [16], which considered the adoption of the Nash Bargaining Scheme (NBS) [17] as a way of reducing the potentially high inefficiency of the Nash Equilibrium. 1 Nevertheless, the NBS only contemplates two scenarios, namely the "grand coalition" (i.e., an agreement reached by all agents) and the disagreement point, i.e., the outcome of the fully non-cooperative scenario.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation